Impact of pulmonary rehabilitation on exercise capacity, health-related quality of life, and cardiopulmonary function in lung surgery patients: a retrospective propensity score-matched analysis - Niu, Chunlai; Lin, Huan; Zhang, Zinan; Wang, Qing; Wei, Yingjun (Frontiers in Medicine, 2024)
Background: Pulmonary rehabilitation is considered beneficial for patients undergoing lung surgery, yet its specific impacts on exercise capacity, health-related quality of life (HRQL), and cardiopulmonary function require further elucidation. This study aimed to evaluate the effect of PR on these outcomes in patients undergoing lung surgery using a retrospective propensity scorematched analysis. Methods: We retrospectively analyzed 420 patients with non-small cell lung cancer (NSCLC) who underwent lung surgery from January 2022 to May 2024. Among these, 84 patients received PR while 336 did not (control group). Propensity score matching (PSM) at a 1:1 ratio yielded 46 patients in each group. Baseline characteristics, spirometry, cardiopulmonary exercise testing, respiratory muscle strength, HRQL, and muscle measurements were assessed pre-and post-surgery. Results: Before PSM, significant differences existed between groups, with the PR group being older and having different pulmonary function baselines. After PSM, groups were well-balanced. Postoperatively, the PR group showed significant improvements in FEV1/FVC (64.17% vs. 50.87%, p < 0.001), FEV1 (2.31 L/min vs. 1.75 L/min, p < 0.001), and predicted FVC percentage (88.75% vs. 68.30%, p < 0.001). Cardiovascular responses showed a lower CI during exercise in the PR group post-PSM (6.24 L/min/m2 vs. 7.87 L/min/m2, p < 0.001). In terms of exercise capacity, the PR group had higher maximal WR percentage (104.76% vs. 90.00%, p = 0.017) and peak VO2 (1150.70 mL/min vs. 1004.74 mL/min, p = 0.009). PR also resulted in less leg soreness and lower total CAT scores postoperatively. Muscle measurements indicated significantly smaller reductions in ΔHUESMCSA and percentage change in the PR group. Conclusions: Pulmonary rehabilitation significantly enhances exercise capacity, HRQL, and cardiopulmonary function in patients undergoing lung surgery. It also mitigates postoperative muscle loss, underscoring its importance in the postoperative management of lung surgery patients.